Understanding HIV/AIDS Prevalence in Salatiga City, Central Java: 2021-2023 Epidemiological Report - A'yun Hafisyah Wafi; Yulietta Avianty; Wahyu Hudoyoko; Bayu Satria Wiratama (BKM Public Health and Community Medicine, 2024)
Purpose: The aim of this study is to describe the epidemiology of HIV/AIDS cases in Salatiga City, Central Java. Methods: This study utilized secondary data from HIV/AIDS Information System (SIHA) of Salatiga from 2021-2023. Data were analyze descriptively according to risk factors and characteristics. Populations at-risk are FSWs (Female Sex Workers), MSM (Male Sex Male), transgenders, STI (Sexually Transmitted Infection) patients, Intravenous Drug Users, pregnant woman, TB patients and prison inmates. Results: During 2021-2023, 294 new HIV/AIDS cases were found in Salatiga City. Screening was conducted regularly to this at-risk-populations with the results of the positivity rate as follows: 0.06% among pregnant women; 3.5% among TB patients; 0.9% among FSWs; 3% among MSM; 0.5% among IDUs; and 0% among other groups. During this period, HIV/AIDS transmission was most prevalent among MSM (69%), followed by TB patients (17%) and FSWs (9%). From all of HIV/AIDS in 2021-2023, the the transmission was more prevalent among men (77%). Based on age group, early to late adulthood with age range of 26-45 years had the highest proportion (48%), followed by aged ≥46 years (29%). The percentage of people living with HIV/AIDS (PLWHA) who initiated ART in 2021 was only 66%, in 2022 was 90%, and in 2023 was 98%. However, by December 2023, based on the cascade, there were only 276 PLWHA (15% of the estimated) were on ART. Most of HIV/AIDS cases were diagnosed at Ario Wirawan Lung Hospital (43%) and Salatiga General Hospital (26%). Conclusions: This study highlights the trends and gaps in epidemiology of HIV/AIDS in Salatiga with high prevalence among MSM, TB patients and adults aged 26-45. Despite improvements in ART initiation from 2021 to 2023, continous treatment of PLWHA remains a challenge. Targeted interventions, expanded screening, and enhanced health facility capacities are crucial to adress this problem.